Recent changes in welfare indicators among Palestinian refugees in Lebanon: a comparative study of two cross-sectional datasets. (March 2019) - Salti, Nisreen; Chaaban, Jad; Ghattas, Hala; Irani, Alexandra; Seyfert, Karin; Ismail, Tala; Khedr, Salma
Abstract: Background: Palestinians in Lebanon have been protracted refugees for 70 years, but the Syrian crisis has caused shocks that threaten to destabilise their already fragile livelihoods. Over a million Syrian refugees and 42 000 Palestinian refugees from Syria have fled to Lebanon, adding pressure to an already weak infrastructure and labour market. The United Nations Relief and Works Agency (UNRWA), the main provider of health, education and relief services to Palestinian refugees, is exceptionally strained. This study examines changes in education, health, employment, food security, and poverty indicators for Palestinian refugees in Lebanon (excluding Palestinian refugees from Syria) using two nationally representative household surveys conducted in April, 2010, and July, 2015. Methods: The surveys were conducted using multi-stage cluster random sampling. Both surveys included households residing in camps and gatherings. Health conditions were reported for all household members by a proxy survey respondent from among the household members. Food insecurity was assessed using the Arab Family Food Security Scale. The poverty lines (thresholds) were set at US6·84 per person per day (upper poverty line) and US2·47 per person per day (extreme poverty line) in 2015, and US6 per person per day (upper poverty line) and US2·17 per person per day (extreme poverty line) in 2010. The difference across the 2 years reflects adjustment for inflation rates within the 5-year period. Data were analysed using STATA13. The study was approved by the Institutional Review Board of the American University of Beirut. Informed verbal consent was obtained from the survey respondents. Findings: Of the eligible sampled households of Palestinian refugees in Lebanon, 88% (2974 of 3382) in 2015 and 99% (2593 of 2626) in 2010 gave informed consent and completed the questionnaire. Net enrolment rates for elementary education remained high (98% in 2015 and 95% in 2010), but failed to lead to better labour market outcomes. The unemployment rate increased from 8% in 2010 to 23% in 2015, and the fraction working in elementary occupations increased from 23% to 36%. Overall poverty remained unchanged but with considerable regional shifts: poverty increased by 9% and 11% in central Lebanon and north Lebanon, respectively, whereas it dropped by 8% and 9% in Saida and Tyre. Extreme poverty was halved from 7% to 3%. There was a high prevalence of chronic diseases in both years (37% in 2015 and 31% in 2010); and in 2015, out-of-pocket health expenditure was six times higher when the household reported at least one chronic condition (US50·9 per capita per month compared with US8·3 per capita per month). Despite the reduction in extreme poverty, 4% of households shifted from moderate to severe food insecurity. Interpretation: Pressures on UNRWA services come at a time when the organisation is operating with a large shortfall in funding. Recent US funding cuts may have dire repercussions for a population burdened by a high prevalence of chronic conditions and facing high healthcare costs. With additional budgetary strains and worsening labour market conditions, Palestinian refugees in Lebanon risk losing some of the ground that they have gained in net enrolment rates in education, access to health-care services and the reduction in extreme poverty that the UNRWA has worked towards for decades. Funding: UNRWA funded the data collection for both surveys.